The power of House + Home: exploring a capabilities approach to housing and prosperity in Kenya - Layseca, Marisol (2024)
This paper explores the role of housing in the achievement of prosperity from a capabilities perspective. Prosperity, according to Jackson (Prosperity without growth: economics for a finite planet, Earthscan, Oxford, 2009), is built on Amartya Sen’s notion of capabilities for flourishing. Then, in the pursuit of understanding the role of housing as an enabler of capabilities for the achievement of prosperity, this paper investigates the gaps in the views/concepts of housing through comparisons of the ten central capabilities, the right to adequate housing, and meanings of home. Data from a recent qualitative study in rural and urban Kenya is used for empirical analysis as a way to develop a localised application of the discussion. Looking through the lens of the Capabilities Approach brought a useful framework that made it possible to capture human and social housing values that are many times neglected. In that sense, the paper explores housing both as the physical conditions of the house and as the social and psychological dynamics that construct the meanings of home. The research demonstrated that the extent to which housing enables the enjoyment of capabilities for flourishing increases or diminishes insofar housing acknowledges and incorporates both material and non-material functions. Hopefully, this exercise can serve to inform and enrich future localised housing design, research and policy, where a more comprehensive understanding and conceptualisation of housing seems imperative: Housing, as House + Home.